Development of a 70 MHz unit for hyperthermia treatment of deep-seated breast tumors. Issue 6 (24th May 2017) - Crezee, Johannes; Van Tienhoven, Geertjan; Kolff, Merel W.; Sijbrands, Jan; Van Stam, Gerard; Oldenborg, Sabine; Geijsen, Elisabeth D.; Hulshof, Maarten C.C.M.; Kok, Henny P.
Abstract : A dedicated hyperthermia (HT) system was designed for tumors in intact breast extending beyond the heating depth of our superficial 434 MHz antennas, consisting of a treatment bed fitted with a 50 cm × 40 cm × 16 cm temperature controlled open water bolus. The patient lies in prone position with the breast immersed in the water positioned in front of a 34 cm × 20 cm 70 MHz waveguide operating in the TE10 mode. E-field patterns were measured in a tissue-mimicking phantom. HT was applied once a week with the 70 MHz applicator for six patients treated with thermoradiotherapy for deep lesions of recurrent breast cancer or melanoma. Two 14-sensor thermocouple thermometry probes were placed in catheters to monitor the invasive temperature. Results: Phantom measurements showed sufficient penetration depth up to 10 cm depth. The combination of 300–900 W antenna power and a water temperature of 42°C was well tolerated for the entire session of 1 h and resulted in good tumor temperatures with T90 = 39.8°C, T50 = 41.1°C, and T10 = 42.2°C. No toxicity or complaints were associated with the heating. A water mattress and other measures were needed to assure a comfortable position throughout the treatment. Conclusion: the 70 MHz breast applicator system performed well and tumor temperatures were good.